DESIGN AND MANUFACTURING OF A WORK SAFETY DEVICE PROTOTYPE FOR MILLING MACHINES - Susilo, Heri; Aji, Muhammad Dava (Center for Study and Journal Management FTI UMI, 2025)
This research focuses on designing and creating a prototype safety device for horizontal milling machines using the Design Thinking method. The study addresses the significant safety concerns in manufacturing environments, particularly the risks associated with operating milling machines, including exposure to metal fragments and direct contact with cutting tools. Through a structured approach following the five stages of Design Thinking (Empathize, Define, Ideate, Prototype, and Test), the researchers developed a flexible safety device tailored to the specific needs of milling machine operators. The prototype was designed to protect operators from metal debris and direct contact with cutting tools while maintaining visibility and productivity. The effectiveness of the prototype was evaluated using the System Usability Scale (SUS) method, with surveys conducted among 30 respondents comprising laboratory assistants and students with experience operating horizontal milling machines. The results showed an average SUS score of 69.25, categorizing the safety device as